Visualization of arrangements of carbon atoms in graphene layers by Raman mapping and atomic-resolution TEM - Cong, Chunxiao (2013)
In-plane and out-of-plane arrangements of carbon atoms in graphene layers play critical roles in the fundamental physics and practical applications of these novel two-dimensional materials. Here, we report initial results on the edge/crystal orientations and stacking orders of bi- and tri-layer graphene (BLG and TLG) from Raman spectroscopy and transmission electron microscopy (TEM) experiments performed on the same sample. We introduce a new method of transferring graphene flakes onto a normal TEM grid. Using this novel method, we probed the BLG and TLG flakes that had been previously investigated by Raman scattering with high-resolution (atomic) TEM.